Oxytocin biases eye-gaze to dynamic and static social images and the eyes of fearful faces: associations with trait autism - Le, Jiao (Transl Psychiatry, 2020)
A key functional effect of intranasal oxytocin with potential therapeutic relevance for autism-spectrum disorder is its reported facilitation of attention towards social stimuli, notably the eye region of faces. In the current randomized placebo-controlled within-subject experiment on 40 healthy males, we investigated the robustness of this facilitation of attention by intranasal oxytocin (24IU) towards social cues. Eye-tracking measures of preference for dynamic and static social vs. non-social stimuli were taken in four different paradigms where autistic individuals tend to exhibit reduced interest in social stimuli. Additionally, we investigated whether oxytocin increases attention towards the eyes relative to other salient face regions in an emotional face paradigm. Results showed that the time spent viewing both dynamic and static social vs. non-social stimuli was negatively associated with trait autism and significantly increased following intranasal oxytocin. For face stimuli, oxytocin primarily increased gaze towards the eyes of fearful expression faces but not for other face emotions. Overall, our findings demonstrate that oxytocin significantly shifts gaze preference towards social vs. non-social stimuli and to the eyes of fearful faces. Importantly, oxytocin appears generally to shift attention more towards salient social stimuli of particular relevance in the context of autism providing further support for its potential therapeutic use in autism-spectrum disorder.